AB0481 AUTOANTIBODIES' TITRE MODULATION BY ANTI-BLYS TREATMENT IN SYSTEMIC LUPUS ERYTHEMATOSUS. (June 2019) - Cavazzana, Ilaria; Kumar, Rajesh; Panaro, Salvatore; Pozzari, Chiara; Ottaviani, Roberta; Fredi, Micaela; Piantoni, Silvia; Andreoli, Laura; Tincani, Angela; Franceschini, Franco
Abstract : Background: Belimumab is a human monoclonal antibody that inhibits soluble B lymphocytes stimulator (BlyS) and represents the only biological drug approved for Systemic Lupus Erythematosus (SLE) (1). Belimumab is effective in reducing disease activity, number of flares and blocking damage progression (2, 3). Pooled data derived from clinical trials reported a reduction of anti-dsDNA, analysed by ELISA, anti-cardiolipin (aCL) and anti-Sm and anti-ribosomal protein antibodies (2, 4). No data were published on anti-beta2glycoprotein I (GPI) antibodies and other antiENA specificities. Objectives: Our aim was to analyse the effect of Belimumab therapy on high avidity anti-dsDNA, aCL, anti-beta2GPI, and other relevant anti-ENA specificities. Methods: 50 patients with active SLE (mean SLEDAI-2K score: 7, 18;SD:3), with a mean age of 39 years (SD:11) and mean follow-up of 13 years (SD: 7, 8) were enrolled. Sera were collected at Belimumab starting (T0) and every 6 months until 24th month. Disease activity index (SLEDAI-2K) was collected at every timepoints. High avidity anti-dsDNA were detected by radioimmunological method, anti-ENA, anti-cardiolipin (aCL), anti-β2 glycoprotein I (anti-β2GPI) were analysed by ELISA. Results: At baseline 86% of sera were positive for anti-dsDNA, 50% for anti-ENA, 20% for aCL and 28% for anti-beta2GPI. Anti-dsDNA became negative in 21%, anti-beta2GPI IgG in 33% and aCL IgG in 30% of sera, mostly at T6. Among anti-ENA, 6/10 (60%) anti-ribosomal and 3/17 (17.6%) anti-Sm positive sera became negative. A significant decrease of anti-dsDNA and anti-beta2GPI IgM titers were observed at all timepoints. IgG aCL titre showed significant decrease only at T18. Anti-ribosomal showed a significant titre decrease at T6 and T12, with seroconversion to negative at T18. Anti-Sm titre significantly dropped down at T6, then remained stable during time. A significant correlation between anti-dsDNA and anti-ribosomal titre, and between SLEDAI ratio (SLEDAI value/SLEDAI T0) and anti-ribosomal titer ratio (value/value T0) were found. Conclusion: Belimumab treatment induced a significant reduction of SLE-specific autoantibodies titre and IgM anti-beta2GPI. Anti-ribosomal titre decrease correlates with anti-dsDNA titre and improvement of disease activity. References: [1] Stohl W, et al. Nat. Biotechnol. 2012; 30: 69-77. [2] Ginzler EM, Wallace et al. J Rheumatol 2014; 41:300-9. [3] Iaccarino et al. Arthritis care Res 2017; 69: 115-123. [4] Stohl W, et al. Arthritis Rheum 2012; 7: 2328-37. Disclosure of Interests: Ilaria Cavazzana: None declared, Rajesh Kumar: None declared, Salvatore Panaro: None declared, Chiara Pozzari: None declared, Roberta Ottaviani: None declared, Micaela Fredi: None declared, Silvia Piantoni: None declared, Laura Andreoli: None declared, Angela Tincani Consultant for: UCB, Pfizer, Abbvie, BMS, Sanofi, Roche, GSK, AlphaSigma, Lillly, Jannsen, Cellgene, Novartis, Franco Franceschini: None declared